Removal of antibiotic resistance genes during livestock wastewater treatment processes: Review and prospects - Huang, Feng; Hong, Yanting; Mo, Chunhao; Huang, Peier; Liao, Xindi; Yang, Yiwen (Frontiers in Veterinary Science, 2022)
Antibiotic resistance genes (ARGs) are emerging pollutants that have received extensive attention. Many different types of ARGs exist in livestock wastewater. If not effectively treated, they can threaten animal production, public health and the ecological safety of the surrounding environment. To address the high risk of livestock wastewater contamination by ARGs, the effects of different wastewater treatment processes on ARGs and their influencing factors and mechanisms are reviewed herein. Additionally, the current problems associated with removal of ARGs are discussed, and future research is proposed.